Macrolide-Resistant Mycoplasma pneumoniae Infections among Children after COVID-19 Pandemic, Ohio, USA - Amy L. Leber; Tori Embry; Kathy Everhart; Jeanette Taveras; Sophonie J. Oyeniran; Huanyu Wang (Emerging Infectious Diseases)
Mycoplasma pneumoniae infections decreased in Ohio, USA, during the COVID-19 pandemic but reemerged in 2023; >2,000 cases were reported during September 2023–September 2024. Of 995 M. pneumoniae–positive samples, 24 (2.4%) had mutations for macrolide-resistant M. pneumoniae (MRMp). MRMp rates are low but increasing. MRMp surveillance is crucial for monitoring antimicrobial resistance.